VALUE OF NATIONALISM ACTIVIST ROHIS - Ashif Az Zafi (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Having a Nationalism Value is a duty for every citizen. In other words, it is an unconditional value. At the same time, the issue of racial disunity has been grown lately. This issue is related to religion. Most compelling evidence, high school student’s Nationalism Value moreover theirs who follow spiritual organization has been descending due to the incorporation between religion and nationality. The scope of this field research is within SMA Negeri 1 Purworejo. Qualitative analysis method supported by descriptive statistical data is being used in this study. As a result, this research found that Nationalism Value can be instilled through classroom learning, recitation and activities in the spiritual program. The value of Unity and Patriotism, which constitutes for Nationalism Value, is invested through verbal and non verbal communication. For this reason, Islamic religion teacher is the most crucial agent in instilling Nationalism Values to spiritual activists. In the event that 57% of students have a high Unity Value and 68% of students have high Patriotism Value, henceforth the Nationalism's Value of spiritual activists tends to be high.